2017
DOI: 10.1039/c6ra28211c
|View full text |Cite
|
Sign up to set email alerts
|

Photochirogenic nanosponges: phase-controlled enantiodifferentiating photoisomerization of (Z)-cyclooctene sensitized by pyromellitate-crosslinked linear maltodextrin

Abstract: The enantioselectivity of the photoisomerization of (Z)-cyclooctene sensitized by the linear maltodextrin-based nanosponges are critically dependent on the phase properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…MD is in widespread use because it is nontoxic even when consumed in excessive quantities and is inexpensive. Previous studies have shown that the gelling ability of κ-CRG can be improved by cross-linking CRG with MD [14][15][16]. Hence, we opined that MD is able to modify CRG's structure to reduce the brittleness of the capsules.…”
Section: Introductionmentioning
confidence: 85%
“…MD is in widespread use because it is nontoxic even when consumed in excessive quantities and is inexpensive. Previous studies have shown that the gelling ability of κ-CRG can be improved by cross-linking CRG with MD [14][15][16]. Hence, we opined that MD is able to modify CRG's structure to reduce the brittleness of the capsules.…”
Section: Introductionmentioning
confidence: 85%
“…Cyclodextrin-based nanosponges (βCD.NS) are the groups of hyper-branched polymers which can be obtained by the reaction of cyclodextrins with crosslinking reagents such as dialdehydes, dialkyl carbonates, carbonyldiimidazoles, epichlorohydrine, urethane, citric acid, diisocyanates, etc [1][2][3][4][5][6]. The inside cavity of cyclodextrins is hydrophobic, while the outer shell is highly hydrophilic, thus cyclodextrins 1 3 are able to form stable host-guest complexes with molecules of suitable polarity and size even in aqueous solutions [7,8], thereby these compounds have various applications in several fields such as catalysis, pharmaceuticals industries, biomedical, drug carrier systems, nanoreactors, molecular recognition, waste treatment, separation, electrochemical sensors, optical and electrical devices [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Manipulating the physical properties and chemical reactivity of organic molecules through non-covalent interactions is one of the most crucial goals in current photochemistry and supramolecular chemistry. , Through the formation of a supramolecular assembly, guest molecule(s) are spatially confined, orientationally aligned, conformationally restricted, and locally concentrated in the limited space of the host cavity to alter the original properties and reactivities. Indeed, (chiral) molecular hosts, such as cyclodextrins, cavitands, cucurbiturils, coordination cages, and hydrogen-bonding templates, have been employed for controlling excited-state properties and reactivities through supramolecular assembly to achieve substantial changes in chiroptical properties and stereochemical outcomes in chirality sensing and photochirogenesis. …”
Section: Introductionmentioning
confidence: 99%